THE BENEFITS OF ARCHIVES IN HANDLING THE COVID-19 PANDEMIC: Array - 1 (Jurnal Kearsipan, 2021)
The high number of neglectful phenomena in social distancing to prevent the spread of Corona Virus Disease 2019 (Covid-19) in Indonesia is an example of how distant our nation from memories when we experienced something similar, namely the 1918 Spanish Flu pandemic. This paper describes the benefits of archives in facing the Covid-19 pandemic. Those benefits are inseparable from the special ability of the archives to provide communication between humans beyond generations. The archives that recorded disaster events could be the references for disaster management and assets for mitigation. Likewise, in the face of the Covid-19 pandemic that occurred during the massive development of information and communication technology that tore apart time and place barriers, archives needed to move globally to present their benefits in tackling the pandemic. This paper was arranged using qualitative research methods and historical approaches.